Aprendizagem de frações por meio de aplicativos gamificados - Nascimento, Flaviano Gomes (2023)
This research was designed with the aim of identifying whether there is a relationship between interaction with gamified applications and learning fractions. The participants were students in the 7th year of elementary school at a public school located in the interior of the state of Bahia. It was qualitative research, with bibliographical, exploratory and descriptive aspects and the data were collected through the application of diagnostic evaluations, in addition to the application of a sequence of activities in the classroom with the use of gamified applications. As fundamentals, we essentially use the concepts of gamification and gamification in learning, in addition to the concept of fraction and the difficulties faced in learning them. With regard to data analysis, it was decided to use the Content Analysis technique, which was carried out through observation and revisions based on the three stages of organization of an analysis, namely: pre-analysis, material exploration and treatment. of the results. Among the results obtained, we can point out that there was a significant improvement in the students' performance in relation to some of the operations with fractions and their representation, pointing to the existence of a relationship between the use of gamified applications and the learning of fractions.